Analisa Kinerja Lalu Lintas Akibat Pembangunan Underpass di Jalan Jenderal Sudirman Kota Ambon - Syaharani Maruapey; Anthoneta Maitimu; Ruben Kumbangsila (KOLONI, 2024)
Underpass in the infrastructure sector is a path / road that is under the ground or under a bridge. Underpass serves to minimize the problem of traffic jams that often occur in several capital cities in Indonesia. One of them is the capital city of Maluku Province, namely Ambon City. Therefore, accessibility in Ambon City must be improved by providing a transportation network system such as underpasses. In this study, primary and secondary data were collected before an after the underpass on Monday – Sunday at 06.00 – 18.00 wit. Furthermore, the data is analyzed, followed by the calculation of the road capacity to the degree of satu ration. So that I can be seen the performance of traffic on Jalan Jenderal Sudirman before and after the underpass. Based on survey data, analysis, and calculation, traffic performance on the general Sudirman road before the underpass in 2019 obtained the highest density level with the value of capacity (C) = 1564 pcu/hour, traffic flow (Q) = 2730 pcu/hour, and the degree of saturation (DS) > 1.75 pcu/hour at the peak hour of the afternoon. Meanwhile, traffic performance after the underpass in 2020 obtained the highest density level with the value of capacity (C) = 1470 pcu/hour, traffic flow (Q) =1232 pcu/hour, and the degree of saturation (DS) > 0.84 pcu/hour at the peak of the afternoon The average degreeof saturation (DS) = 1.23 pcu/hour before the underpass and (DS) = 0.53 pcu/hour after the underpass. So the traffic performance after the underpass decreased by 43.1% from the performance before the underpass